Low-cost modular remote-control system for two-wheel hand tractors: design and performance evaluation using fly sky fs-i6 - Rizky Tirta Adhiguna; Syifa Robbani; Amin Rejo (Politeknik Negeri Lhokseumawe, 2025)
This research designed and developed a modular remote-control system for two-wheel hand tractors using the Fly Sky FS-i6 transmitter as a low-cost and responsive alternative to existing automation solutions. The primary objective is to improve operational efficiency and operator comfort while maintaining investment costs suitable for Indonesian smallholder farming. The total cost of system components (DC motors, servo motors, relays, solenoids, and receivers) was approximately USD 210, which is significantly lower than comparable IoT- or GPS-based automation kits (USD 600–1,000). Modifications were made to the throttle, clutch, and brake systems, allowing for remote operation via radio frequency without requiring the replacement of the main engine. Performance testing was conducted on various land conditions, measuring response time, tractor speed, theoretical and practical capacity, working efficiency, ploughing depth, wheel slip, and fuel consumption. Results showed that the solenoid-based control system responded reliably with an average delay of 1.5 seconds across all throttle positions. Average working speeds for throttle positions of 3 cm, 6 cm, and 9 cm were 1.872 km/h, 2.628 km/h, and 3.096 km/h, respectively. Wheel slip remained within the SNI standard of ≤ 25%, and fuel consumption averaged 0.33 liters per hour. Straight-line motion tests revealed a maximum deviation of 240 cm on uneven soil surfaces. This deviation is considered acceptable for hand tractor operations in Indonesia, where plot widths typically range from 15–25 m, and does not significantly reduce working efficiency. Overall, the modular remote-control system significantly improves usability and efficiency while providing a scalable, low-cost transition toward precision agriculture technologies in smallholder farming contexts.